A novel determination of curcumin via Ru@Au nanoparticle decorated nitrogen and sulfur-functionalized reduced graphene oxide nanomaterials. Issue 2 (15th December 2015) - Kotan, Gül; Kardaş, Faruk; Yokuş, Özlem Aktaş; Akyıldırım, Onur; Saral, Hasan; Eren, Tanju; Yola, Mehmet Lütfi; Atar, Necip
Abstract : We report the synthesis of Ru@Au nanoparticles involvedl -cysteine functionalized reduced graphene oxide (rGO) composites (NSrGO/Ru@AuNPs). Abstract : We report the synthesis of Ru@Au nanoparticle involvedl -cysteine functionalized reduced graphene oxide (rGO) composites (NSrGO/Ru@AuNPs). The nanocomposites were characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical determination of curcumin (CR) has been studied using square wave voltammetry (SWV) on a glassy carbon electrode (GCE) modified with NSrGO/Ru@AuNP composites (NSrGO/Ru@AuNPs/GCE). The effective surface areas (ESAs) of the rGO/GCE and NSrGO/Ru@AuNPs/GCE were calculated to be 347 cm 2 mg −1 and 1289 cm 2 mg −1, respectively. These results show that the electrochemical surface area of the NSrGO/Ru@AuNPs/GCE is 3.71 times higher than that of the rGO/GCE. The developed method was also applied successfully for the determination of CR in plasma and the linearity range of CR was 0.001–0.1 nM with a detection limit of 2.0 × 10 −13 M.